Rethinking the Education Paradigm in Morocco in the Covid-19 Context- Assessment of Resilience Curricula in Higher Education - Zineb Birrou; Aziz Kich; Mohammed Larouz (English Department, Faculty of Humanities, Andalas University, 2021)
The Covid-19 pandemic has impacted mental and emotional health in significant ways, and has worsened the already existing crisis of rising anxiety, chronic stress and depression among the youth. This was particularly marked by the drastic lockdown measures, the incessant stream of bad news, and the sudden shift to online education. Faced with stressors, resilience is a skill-set that aids with adapting, coping, and bouncing back from adversity while maintaining or quickly returning to a relatively healthy psychological functioning. This article therefore aims to explore the past, present and future situation regarding emotional and mental resilience skills in Moroccan higher education curricula. To this end, structured and semi-structured interviews have been conducted with four senior officials at the Ministry of Education in Rabat, Morocco. Furthermore, surveys have been collected from faculty members in eight public universities. The findings reveal that resilience education has not been officially implemented yet in Moroccan universities. However, the national vision shows the rising awareness in the need to shift to a more holistic educational paradigm, especially in light of the Covid-19 pandemic, to better prepare students for the uncertain and fast-changing future.